2013
DOI: 10.1007/s00404-013-3045-z
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Pap screening among Israeli women, 2005–2010

Abstract: The increase in the rate of squamous cell abnormalities demonstrated in this study emphasizes the need of implementing an education and a screening program among Israeli women. HPV vaccine, sexual behavior, cytology performance and HPV test are primary and secondary prevention tools which may reduce morbidity and mortality in the future. In addition, based on the age at diagnosis of the different pathologies, the age group in which Pap test is performed in Israel should be expanded from 35-54 to 25-65 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 21 publications
5
14
2
2
Order By: Relevance
“…In other studies, the rate of HSIL has been given as 0.34-1.18%. 10,19 HSIL was observed less frequently in our country compared to the numbers in the literature. The incidence of HSIL was found to be 0,17 in a multicentre study.…”
Section: Statisticscontrasting
confidence: 76%
See 4 more Smart Citations
“…In other studies, the rate of HSIL has been given as 0.34-1.18%. 10,19 HSIL was observed less frequently in our country compared to the numbers in the literature. The incidence of HSIL was found to be 0,17 in a multicentre study.…”
Section: Statisticscontrasting
confidence: 76%
“…17 In another study which examined 711000 Pap smear results from Israel, it was specified as 2.72%. 10 In our study, ASC-US was observed most often between the ages of 21-45 (1.32%). ASC-US was observed most often at the age of 42 in this age group (4.21%).…”
Section: Statisticssupporting
confidence: 46%
See 3 more Smart Citations